Endohelminth fauna of the marsh frog Rana ridibunda from Lake Hazar, Turkey - Saglam, Naim; Arikan, Hatice (Inter-Research, 2006)
In this study, 236 marsh frogs Rana ridibunda collected from Lake Hazar (Elazig, Turkey) at 15 d intervals between March 2001 and February 2002 were examined for endohelminths; of these, 148 (62.71%) frogs were found to be infected with helminths. In total, 9 helminth species (3 trematodes, 5 nematodes and 1 acanthocephalan) were identified. We observed Gorgoderina vitelliloba (prevalence 2.97%) in the urinary bladder, Haematoloechus variegatus (4.66%) and Rhabdias bufonis (8.90%) in the lung, Pleurogenoides medians (1.69%), Oswaldocruzia filiformis (3.81%) and Acanthocephalus ranae (26.27%) in the small intestine, Neoxysomatium brevicaudatum (16.95%) and Cosmocercoides sp. (3.39%) in the large intestine, and Eustrongylides excisus (14.41%) in the body cavity and on the stomach. No helminth was found in the spleen, kidney, gall bladder, liver, heart or muscle. Of the 9 helminth species identified, Acanthocephalus ranae (26.27%) had the highest prevalence and abundance and Oswaldocruzia filiformis (8.33 +/- 4.09) had the highest mean intensity.
Keywords: Rana ridibunda; endohelminths; Gorgoderina; Haematoloechus; Rhabdias; Pleurogenoides; Oswaldocruzia; Acanthocephalus; Neoxysomatium; Cosmocercoides